1986
DOI: 10.3354/meps029141
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bacteria and zooflagellates on the composition of sinking particles: an in situ experiment

Abstract: Multiple sediment trap (MULTITRAP) arrays were deployed at 3 hydrographically and biologically distinct stations in the eastern North Pacific Ocean and used to evaluate experimentally the hypothesis that protozoan grazers are important in the diagenesis of sinking biogenic materials in the ocean. Measurements were made of adenosine triphosphate (ATP) concentrations and the abundances of bacteria and zooflagellates associated with sinking particles collected from in situ preserved and 2 sets of unpreserved (liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…McCambridge and McMeekin 1980;Newell et al 1983;Sherr et al 1986;Bomo et al 2004), whereas in others, it was found to inhibit aerobic or anaerobic bacteria (Taylor and Pace 1987;Tremaine and Mills 1987). Taylor and Pace (1987) strongly advised caution in the use of eukaryotic inhibitors, and Tremaine and Mills (1987) concluded that cycloheximide should not be used in grazing Ramirez and Alexander (1980) Seston 1 Taylor et al (1986) experiments. Nonetheless, the majority of studies we found that used cycloheximide were published after these stern warnings, and they did not test any of the assumptions.…”
Section: Jeff Shimeta 1* and Perran Lm Cookmentioning
confidence: 99%
See 1 more Smart Citation
“…McCambridge and McMeekin 1980;Newell et al 1983;Sherr et al 1986;Bomo et al 2004), whereas in others, it was found to inhibit aerobic or anaerobic bacteria (Taylor and Pace 1987;Tremaine and Mills 1987). Taylor and Pace (1987) strongly advised caution in the use of eukaryotic inhibitors, and Tremaine and Mills (1987) concluded that cycloheximide should not be used in grazing Ramirez and Alexander (1980) Seston 1 Taylor et al (1986) experiments. Nonetheless, the majority of studies we found that used cycloheximide were published after these stern warnings, and they did not test any of the assumptions.…”
Section: Jeff Shimeta 1* and Perran Lm Cookmentioning
confidence: 99%
“…A literature search yielded over 30 publications (most shown in Table 1), none of which tested all three assumptions thoroughly. Of the studies that did address these assumptions to some extent, most notable are Newell et al (1983), Sherr et al (1986), Taylor et al (1986), Taylor and Pace (1987), Tremaine and Mills (1987), and Tso and Taghon (2006) who evaluated the first and third assumptions in some detail, but only Taylor and Testing assumptions of the eukaryotic inhibitor method for investigating interactions between aquatic protozoa and bacteria, applied to marine sediment…”
mentioning
confidence: 99%
“…In ageing aggregates, senescent algae might not alone be able to provide a sufficient amount of degradable material for the maintenance of high standing stock of attached bacteria. Therefore, the role of 'recycling' of organic matter from microzooplankton (as excretion, dead cells, fecal pellets, sloppy feeding) to bacteria is emphasised as the aggregates get older (Hoppe 1981, Taylor et al 1986, Biddanda & Pomeroy 1988. Cyanobacterial aggregates can stay in the upper water layer for weeks because of their buoyancy and reach a steady state in which in-and output of organic matter is balanced (Hoppe 1981).…”
Section: Bacterial Production and Cell Numbersmentioning
confidence: 99%
“…Recently, Steward et al (1996) presented evidence that viruses may cause substantial mortality of mesopelagic bacterioplankton, but other sources may contribute as well. Several studies reported the ubiquitous occurrence of heterotrophic nanoflagellates (HNF) in the mesopelagial (Pomeroy & Johannes 1968, Taylor et al 1986, Cho & Azam 1988, Steward et al 1996. However, nothing is known about their grazing impact on bacterioplankton.…”
Section: Introductionmentioning
confidence: 99%